Emery & Rimoin's principles and practice of medical genetics:VOL.2 - Rimoin, David L; Ed. Pyeritz, Reed E; Ed (Churchill Livingstone Elsevier, 2007)
"For decades, Emery and Rimoin's Principles and Practice of Medical Genetics has provided the ultimate source for practicing clinicians to learn how the study of genetics can be integrated into practice. With advances in high-throughput technologies propelling the closer integration of lab and clinical work, this 6e bridges the gap between high-level molecular genetics and individual application. This comprehensive yet practical resource emphasizes theory and research fundamentals related to applications of medical genetics across the full spectrum of inherited disorders. Clinically oriented information is supported by expanded sections on basic principles of genetics, research approaches, and analytics to embrace the evolving population of students, researchers, and practitioners who are integrating their work to provide advanced diagnosis, prevention and treatment of human disease. Over 250 of the world's most trusted authorities in medical genetics will contribute to the new release of the revised electronic edition of the work. Regular updates and the integration of teaching tools such as videos and graphics will distinguish this work from the competition. Links to sites such as Online Mendelian Inheritance in Man (OMIM) and similar sites that provide up-to-date information on human genes and genetic phenotypes will make this product the ultimate source for students, researchers, and practitioners alike."--Publisher's website.